Capacity and technology selection via cost modelling in Turkish cement industry - Omay, E. Orhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1992., 1992)
Discounted Cash Flow and Net Present Value methods have been used for analyses in Turkish Cement Industry to provide valuable help for prospective investors in crucial aspects such as selecting proper technology, capacity etc.given the relevant data on equipment, raw material and production costs. Both DCF and Net Present Value methods are heavily dependent upon compilation of relevant technological and economical data, hence a through market and literature survey has been conducted to establish a sound data base.Compiled economical data include costs of raw and operating materials, costs of individual equipment items as a function of capacity, past, present and future trends in cement consumption and production both in Turkey and abroad. As for technological information, main technological parameters such as electrical energy consumption per unit production etc, for each available technology and effects of efficient operation on these parameters have been compiled. The compiled information has been evaluated via DCFROI and NPV methods utilizing a software package; Microsoft Works. Sensitivity analyses on important parameters have also been carried out. Results indicate that a capacity of 1500 tons / clinker is the minimum to be employed in a new investment, regardless of the selected processing scheme. As for the proper processing scheme, selection between processes with and is highly dependent on the efficiency of actual plant oparation.
Keywords: Cement industries -- Turkey.; Cement industries -- Economic aspects.